Working with People Experiencing Homelessness in Europe. Issue 4 (8th August 2022) - Gaboardi, Marta; Santinello, Massimo; Disperati, Francesca; Lenzi, Michela; Vieno, Alessio; Loubière, Sandrine; Vargas-Moniz, Maria J.; Spinnewijn, Freek; Greenwood, Ronni Michelle; Wolf, Judith R.; Bokszczanin, Anna; Bernad, Roberto; et al.
ABSTRACT: In Europe, the widespread transition from the Traditional Staircase (TS) model to the Housing First (HF) model is transforming the way social service providers work with people experiencing homelessness. This study examined social service providers' perspectives in both models regarding factors that facilitate or hinder their work. Data were collected through 17 photovoice projects involving 81 social service providers from eight European countries. The results show factors affecting social service providers' work at three levels: systemic, organizational, and individual. Professionals in TS and HF identified similar topics; however, TS providers discussed more obstacles to work. Implications for practice are discussed.